Liquid metal composite material and preparation method thereof

By adding diamond particles to liquid metal-based thermal interface materials and forming scale graphite bridged channels, the problems of existing materials drying up and filling particles in high temperature environments are solved, and liquid metal composite materials with high thermal conductivity and stability are achieved .

CN119432332APending Publication Date: 2025-02-14CHONGQING COLLEGE OF ELECTRONICS ENG
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411572331.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing liquid metal-based thermal interface materials are prone to react in high temperature environments and cause drying, and the filler particles are high and single, affecting their thermal conductivity and use stability.

Method used

By adding diamond particles to the liquid metal and forming a scale graphite bridge channel therebetween, the thermal conductivity of the liquid metal is enhanced, and the heat transfer path is improved through the interface between the scale graphite and the liquid metal.

Benefits of technology

It significantly improves the thermal conductivity of liquid metals, reduces the content of fill particles, and improves the stability and economical use of materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119432332A_ABST
    Figure CN119432332A_ABST
Patent Text Reader

Abstract

The invention relates to a liquid metal composite material and a preparation method thereof.The method comprises the steps that firstly, a small amount of liquid metal is mixed with diamond particles till the diamond particles are completely wrapped by the liquid metal to form diamond liquid metal, then crystalline flake graphite is mixed with the diamond liquid metal, and the diamond liquid metal is formed; the crystalline flake graphite is used for forming bridging among diamond particles, finally, a certain amount of liquid metal is added to form the liquid metal composite material with the crystalline flake graphite bridging diamond particles, bridging is formed through a very small amount of the crystalline flake graphite, the heat-conducting property of the liquid metal is greatly enhanced, and the heat-conducting property of the liquid metal is greatly improved. Therefore, the composite material has advantages in the field of thermal management of high-power electronic products. Through experimental verification of the applicant, the heat conductivity of the crystalline flake graphite bridged diamond particle liquid metal composite material prepared through the method can reach 80-133W / mK.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of thermal conductive materials, and in particular relates to a liquid metal composite material and a preparation method thereof. Background Art

[0002] As the power density of electronic devices continues to rise, the problem of chip heat dissipation has become increasingly prominent, seriously affecting the performance and stable operation of the chip. In this context, the research and application of thermal interface materials have become the key to solving the problem of chip heat dissipation. It can significantly improve the heat dissipation efficiency of the chip, effectively reduce the chip temperature, and thus enhance the performance of the chip, ensure its reliability, and extend its service life. However, the current application of thermal interface materials is not smooth sailing, and still faces many thorny problems, such as inconsistent thermal conductivity, difficult adhesion, and complex and difficult processing. These problems are like checkpoints, which seriously restrict the widespread application and promotion of thermal interface materials. In view of this, how to overcome these difficulties, optimize the performance of thermal interface materials and enhance their stability has become one of the key directions in the current field of chip heat dissipation research.

[0003] Liquid metal-based thermal interface materials are a new type of thermal interface material with excellent thermal conductivity and good plasticity. For this reason, liquid metal-based thermal interface materials are widely used in the heat dissipation system of high-power electronic equipment. However, there are some problems and defects in existing liquid metal-based thermal interface materials. First, due to the large surface tension of liquid metal, liquid metal-based thermal interface materials are not easy to spread when used, and are prone to leakage. Secondly, most of the existing liquid metal-based thermal interface materials use metal particles as the filling phase, which makes it easy to react in a high temperature environment, causing the liquid metal to dry up, thereby shortening the service life. In addition, inorganic non-metallic particles are also used for liquid metal reinforcement phases, but their interface bonding has a great impact on the long-term use stability of liquid metal composite materials. At present, the content of filling particles required for existing liquid metal-based thermal interface materials is relatively high, and the filling particles are relatively single. Therefore, it is urgent to develop a new type of liquid metal-based thermal interface material to resolve the problems and defects of the existing technology. Summary of the invention

[0004] In view of the deficiencies in the prior art, the present invention proposes a liquid metal composite material and a method for preparing the same. The method enables flake graphite to form a bridging channel between liquid metal-coated diamond particles to enhance the thermal conductivity of the liquid metal, thereby solving the problems in the prior art of high interface binding energy of liquid metal composite inorganic non-metallic particles and insufficient thermal conductivity of the current composite materials.

[0005] The objective of the present invention is achieved through the following technical solutions:

[0006] A method for preparing a liquid metal composite material comprises the following steps:

[0007] 1) stirring the liquid metal and the diamond particles uniformly to obtain a mixture of liquid metal and diamond particles;

[0008] 2) centrifuging the mixed solution obtained in step 1) to separate excess liquid metal and obtain diamond@liquid metal particles;

[0009] 3) mixing the diamond@liquid metal particles and the flake graphite to obtain a diamond@liquid metal / flake graphite mixture;

[0010] 4) The diamond@liquid metal / flake graphite mixture obtained in step 3) is mixed with the liquid metal separated in step 1) to obtain a liquid metal composite material of flake graphite bridging diamond particles.

[0011] Furthermore, the mass ratio of the liquid metal:diamond particles:flake graphite is (69.4-72.1):(27.5-28.6):(0.4-2.2).

[0012] Furthermore, the liquid metal in step 1) is pure gallium, or eutectic gallium-indium alloy, or gallium-indium-tin alloy.

[0013] Furthermore, the particle size of the diamond particles in step 1) is 50 μm-150 μm.

[0014] Furthermore, the centrifugal speed in step 2) is not less than 3000 rpm.

[0015] Furthermore, the size of the flake graphite in step 3) is 80-100 mesh.

[0016] The liquid metal composite material is prepared according to the above method.

[0017] Compared with the prior art, the present invention has the following advantages:

[0018] 1. The present invention relates to a liquid metal composite material and a preparation method thereof, wherein isotropically conductive diamond particles and anisotropically conductive flake graphite are added to synergistically enhance the thermal conductivity of the liquid metal.

[0019] 2. In the preparation method of the liquid metal composite material of the present invention, flake graphite forms a bridging channel between the diamond particles coated with liquid metal. The flake graphite itself carries functional groups, so that the flake graphite and the liquid metal form an effective interface bonding, thereby greatly improving the thermal conductivity of the liquid metal by improving the heat transfer path.

[0020] 3. The method of the present invention uses diamond particles as the filling phase and surface-treated inorganic non-metallic flake graphite as the reinforcing phase. The particles are not single and the content is low. The economic efficiency is high and the thermal conductivity of the liquid metal is greatly improved. The applicant has experimentally verified that the thermal conductivity of the liquid metal composite material of flake graphite bridged diamond particles prepared by the method of the present invention can reach 80-133W / mK. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the specific embodiments of the present invention, the drawings required for use in the specific embodiments or the description of the prior art will be briefly introduced below.

[0022] Figure 1 This is a process principle diagram of the liquid metal composite material provided by the present invention.

[0023] Figure 2 These are the microscopic morphology pictures of flake graphite, diamond, diamond@EGaIn, EGaIn / diamond / flake graphite of Example 1 of the present invention, the microscopic morphology picture of EGaIn / diamond / flake graphite of Example 2, and the microscopic morphology picture of EGaIn / diamond / flake graphite of Example 3.

[0024] Figure 3 These are the SEM images of EGaIn / diamond / flake graphite of Example 2 of the present invention and the SEM images of Ga / diamond / flake graphite of Example 4 of the present invention.

[0025] Figure 4 This is a comparison chart of the thermal conductivity of the liquid metal composite materials of Examples 1-5 of the present invention and Comparative Examples 1-3. DETAILED DESCRIPTION

[0026] The present invention is further described in detail below in conjunction with the accompanying drawings, the purpose of which is to better understand the content of the present invention rather than to limit the protection scope of the present invention.

[0027] The present invention provides a general and / or specific description of the materials and test methods used in the experiment. The test methods or test methods involved are all conventional methods unless otherwise specified; the reagents or instruments used are all conventional products available on the market, prepared or used in a conventional manner, unless the manufacturer is specified.

[0028] Sources

[0029] Flake graphite: MacLean (Model: G992707).

[0030] Diamond: Zhecheng County Hongxiang Superhard Materials Co., Ltd.

[0031] Liquid Metal: Aladdin.

[0032] The present invention relates to a liquid metal composite material and a preparation method thereof, the principle diagram of which is as follows Figure 1 shown.

[0033] Example 1

[0034] A method for preparing a liquid metal composite material of the present invention comprises the following steps:

[0035] 1) 27.5 g of diamond particles with a particle size of 115 μm were added to 72.1 g of liquid metal eutectic gallium-indium alloy (EGaIn), and the liquid metal and the diamond particles were mixed evenly by stirring to obtain a liquid metal diamond particle mixture.

[0036] 2) The mixed solution obtained in step 1) is subjected to high-speed centrifugation at 4000 r / min to separate excess liquid metal EGaIn, thereby obtaining diamond particles coated with EGaIn (diamond@EGaIn).

[0037] 3) 0.4 g of flake graphite and the diamond@EGaIn obtained in step 2) were mixed evenly to form a diamond@EGaIn / flake graphite mixture.

[0038] 4) The liquid metal EGaIn separated in step 2) is mixed with the diamond@EGaIn / flake graphite mixture in step 3) to obtain a liquid metal composite material of flake graphite bridging diamond particles.

[0039] The present application also conducts a thermal conductivity test on the liquid metal composite material prepared in this embodiment. The measured thermal conductivity is Figure 4 Medium EGaIn / diamond / flake graphite (Example 1), thermal conductivity is 84 W / mK.

[0040] The microscopic morphology of the flake graphite, diamond, diamond@EGaIn, and EGaIn / diamond / flake graphite (Example 1) prepared in this example is shown in FIG. Figure 2 As shown, it can be seen from the figure that the color of EGaIn / diamond / flake graphite is close to the color of liquid metal, that is, silver, because the amount of flake graphite added is small, indicating that the number of diamond particles bridged by flake graphite is small.

[0041] Example 2

[0042] A method for preparing a liquid metal composite material of the present invention comprises the following steps:

[0043] 1) 27.9 g of diamond particles with a particle size of 115 μm were added to 70.8 g of liquid metal eutectic gallium-indium alloy (EGaIn), and the liquid metal and the diamond particles were mixed evenly by stirring to obtain a liquid metal diamond particle mixture.

[0044] 2) The mixed solution obtained in step 1) is subjected to high-speed centrifugation at 3500 r / min to separate excess liquid metal EGaIn, thereby obtaining diamond particles coated with EGaIn (diamond@EGaIn).

[0045] 3) 1.3 g of flake graphite and the diamond@EGaIn obtained in step 2) were mixed evenly to form a diamond@EGaIn / flake graphite mixture.

[0046] 4) The liquid metal EGaIn separated in step 2) is mixed with the diamond@EGaIn / flake graphite mixture in step 3) to obtain a liquid metal composite material of flake graphite bridging diamond particles.

[0047] The present application also conducts a thermal conductivity test on the liquid metal composite material prepared in this embodiment. The measured thermal conductivity is Figure 4 Medium EGaIn / diamond / flake graphite (Example 2), thermal conductivity is 133 W / mK.

[0048] The microstructure of the liquid metal composite material prepared in this embodiment is as follows: Figure 2 As shown in EGaIn / diamond / flake graphite (Example 2), it can be seen from the figure that the color of EGaIn / diamond / flake graphite is between the colors of liquid metal and flake graphite, which means that more flake graphite forms a bridge with the diamond particles, facilitating the rapid conduction of heat.

[0049] The SEM image of EGaIn / diamond / graphite flake prepared in this example is as follows: Figure 3 As shown, the scale bar is 30μm. It can be seen from the figure that the diamond particles and the flake graphite form an effective interconnection, and the flake graphite plays the role of bridging the adjacent diamond particles, thereby forming a high thermal conductivity channel.

[0050] Example 3

[0051] A method for preparing a liquid metal composite material of the present invention comprises the following steps:

[0052] 1) 28.4 g of diamond particles with a particle size of 115 μm were added to 69.4 g of liquid metal eutectic gallium-indium alloy (EGaIn), and the liquid metal and the diamond particles were mixed evenly by stirring to obtain a liquid metal diamond particle mixture.

[0053] 2) The mixed solution obtained in step 1) is subjected to high-speed centrifugation at 4000 r / min to separate excess liquid metal EGaIn, thereby obtaining diamond particles coated with EGaIn (diamond@EGaIn).

[0054] 3) 2.2 g of flake graphite and the diamond@EGaIn obtained in step 2) were mixed evenly to form a diamond@EGaIn / flake graphite mixture.

[0055] 4) The liquid metal EGaIn separated in step 2) is mixed with the diamond@EGaIn / flake graphite mixture in step 3) to obtain a liquid metal composite material of flake graphite bridging diamond particles.

[0056] The present application also conducts a thermal conductivity test on the liquid metal composite material prepared in this embodiment. The measured thermal conductivity is Figure 4 Medium EGaIn / diamond / flake graphite (Example 3), thermal conductivity is 66.9 W / mK.

[0057] The microstructure of the liquid metal composite material prepared in this embodiment is as follows: Figure 2 As shown in EGaIn / diamond / flake graphite (Example 3), it can be seen from the figure that the color of EGaIn / diamond / flake graphite is closer to the color of flake graphite, which means that the amount of flake graphite added is large, and then there is a trend of flake graphite wrapping diamond particles, which will greatly increase the interface thermal resistance and is not conducive to thermal conductivity.

[0058] Example 4

[0059] A method for preparing a liquid metal composite material of the present invention comprises the following steps:

[0060] 1) 28.6 g of diamond particles with a particle size of 115 μm were added to 70.9 g of liquid metal pure gallium (Ga), and the liquid metal and the diamond particles were mixed evenly by stirring to obtain a liquid metal diamond particle mixture.

[0061] 2) The mixed solution obtained in step 1) is subjected to high-speed centrifugation at 4000 r / min to separate excess liquid metal Ga and obtain Ga-coated diamond particles (diamond@Ga).

[0062] 3) 0.4 g of flake graphite and the diamond@Ga obtained in step 2) were mixed evenly to form a diamond@Ga / flake graphite mixture.

[0063] 4) The liquid metal Ga separated in step 2) is mixed with the diamond@Ga / flake graphite mixture in step 3) to obtain a liquid metal composite material of flake graphite bridging diamond particles.

[0064] The present application also conducts a thermal conductivity test on the liquid metal composite material prepared in this embodiment. The measured thermal conductivity is Figure 4 Medium Ga / diamond / flake graphite (Example 4), thermal conductivity is 87 W / mK.

[0065] The SEM image of Ga / diamond / flake graphite prepared in this example is as follows: Figure 3 As shown in the figure, the scale bar is 100μm. It can be seen from the figure that the diamond particles and the flake graphite form an effective interconnection, and the flake graphite plays the role of bridging the adjacent diamond particles, thereby forming a high thermal conductivity channel.

[0066] Example 5

[0067] A method for preparing a liquid metal composite material of the present invention comprises the following steps:

[0068] 1) 27.9 g of diamond particles with a particle size of 50 μm were added to 70.8 g of liquid metal eutectic gallium-indium alloy (EGaIn), and the liquid metal and the diamond particles were mixed evenly by stirring to obtain a liquid metal diamond particle mixture.

[0069] 2) The mixed solution obtained in step 1) is subjected to high-speed centrifugation at 4000 r / min to separate excess liquid metal EGaIn, thereby obtaining diamond particles coated with EGaIn (diamond@EGaIn).

[0070] 3) 1.3 g of flake graphite was mixed evenly with the diamond@EGaIn obtained in step 2) to form a diamond@EGaIn / flake graphite mixture.

[0071] 4) The liquid metal EGaIn separated in step 2) is mixed with the diamond@EGaIn / graphite flake mixture in step 3) to form an EGaIn / diamond / graphite flake composite material.

[0072] The present application also conducts a thermal conductivity test on the liquid metal composite material prepared in this embodiment. The measured thermal conductivity is Figure 4 Medium EGaIn / diamond / flake graphite (Example 5), thermal conductivity is 102 W / mK.

[0073] Comparative Example 1

[0074] Compared with Example 2, in this comparative example, no diamond particles and flake graphite are added, and only 70.8 g of liquid metal eutectic gallium-indium alloy (EGaIn) is added.

[0075] The thermal conductivity of EGaIn in this embodiment was tested. The measured thermal conductivity is shown in Figure 4 The thermal conductivity of EGaIn (Comparative Example 1) is 21 W / mK, which is much lower than the thermal conductivity of the liquid metal composite material of flake graphite bridged diamond particles prepared in Example 2.

[0076] Comparative Example 2

[0077] The preparation method of the liquid metal composite material provided in this comparative example is basically the same as that of Example 2, except that no diamond particles are added, specifically:

[0078] 1.3 g of flake graphite and 70.8 g of liquid metal eutectic gallium-indium alloy (EGaIn) were uniformly mixed to form a mixture of liquid metal EGaIn and flake graphite.

[0079] The thermal conductivity of the mixture of liquid metal EGaIn and flake graphite in this embodiment was tested. The actual measured thermal conductivity is shown in Figure 4 The thermal conductivity of EGaIn / graphite flakes (Comparative Example 2) is 26 W / mK, which is much lower than the thermal conductivity of the liquid metal composite material of graphite flakes bridged with diamond particles prepared in Example 2.

[0080] Comparative Example 3

[0081] The preparation method of the liquid metal composite material provided in this comparative example is basically the same as that of Example 2, except that no flake graphite is added, specifically:

[0082] 27.9 g of diamond particles with a particle size of 115 μm were added to 70.8 g of liquid metal eutectic gallium-indium alloy (EGaIn), and the liquid metal and the diamond particles were mixed evenly by stirring to obtain a liquid metal diamond particle mixture.

[0083] The thermal conductivity of the liquid metal diamond particle mixture of this embodiment was tested. The measured thermal conductivity is shown in FIG. Figure 4 Medium EGaIn / diamond (Comparative Example 3), thermal conductivity is 73 W / mK.

[0084] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. These modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention, and they should all be included in the scope of the claims and specification of the present invention.

Claims

1. A method for preparing a liquid metal composite material, characterized in that: The following steps are involved: 1) stirring liquid metal and diamond particles uniformly to obtain a mixture of liquid metal and diamond particles; 2) centrifuging the mixed solution obtained in step 1) to separate excess liquid metal and obtain diamond@liquid metal particles; 3) mixing the diamond@liquid metal particles and the flake graphite to obtain a diamond@liquid metal / flake graphite mixture; 4) The diamond@liquid metal / flake graphite mixture obtained in step 3) is mixed with the liquid metal separated in step 1) to obtain a liquid metal composite material of flake graphite bridging diamond particles.

2. The preparation method according to claim 1, characterized in that: The mass ratio of the liquid metal: diamond particles: flake graphite is (69.4-72.1):(27.5-28.6):(0.4-2.2).

3. The preparation method according to claim 2, characterized in that: The liquid metal in step 1) is pure gallium, or eutectic gallium-indium alloy, or gallium-indium-tin alloy.

4. The preparation method according to claim 3, characterized in that: The particle size of the diamond particles in step 1) is 50 μm-150 μm.

5. The preparation method according to any one of claims 1 to 4, characterized in that: The centrifugal speed in step 2) is not less than 3000 rpm.

6. The preparation method according to claim 5, characterized in that: The size of the flake graphite in step 3) is 80-100 mesh.

7. A liquid metal composite material obtained according to the method of any one of claims 1 to 6.

Citation Information

Cited By

  • Liquid metal / diamond composite material and preparation method thereof

    CN120945264A